ISU GENDER DAN SERTIFIKASI GURU VERSUS PRESTASI BELAJAR SISWA - Sri Sukarti (LPPM Universitas Terbuka, 2013)
This study aimed to identify achievement differences among elementary student connected with teaching professionalism and gender issues. Samples were retrieved randomly from elementary teachers in District KaranglewasBanyumas Regency consisted of 60 certified teachers and 60 non-certified teachers, in which each group consists of 30 male teachers and 30 female teachers. Data were obtained from the test scores. Results showed nonsignificant differences between the learning outcomes of students taught by certified teachers and students taught by non-certified teacher (tvalue0.789< ttable1.980). Significant differences between the learning outcomes of students taught by male teachers and female teachers (t value4.610)>ttable=1.980). Non significant differences in teaching ability between certified teacher and non-certified teachers. On average male teachers performed better than female groups. Suggested to review the certification system/model to improve teaching profesionalism. Penelitian ini bertujuan mengidentifikasi perbedaan prestasi belajar siswa SD ditinjau dari aspek profesionalitas guru dan isu gender. Sampel ditarik secara acak di Kecamatan Karanglewas Banyumas, terdiri dari 60 guru yang bersertifikat dan 60 guru non-sertifikat, dan masing-masing terdiri dari 30 guru laki-laki dan 30 guru perempuan. Data prestasi belajar siswa diperoleh dari nilai ulangan umum. Hasil analisis data menunjukkan tidak terdapat perbedaan yang signifikan antara hasil belajar siswa yang diajar oleh guru yang sudah bersertifikasi dengan guru yang belum bersertifikasi dengan nilai t hitung0,789, dan ttabel1,980. Terdapat perbedaan yang signifikan antara hasil belajar siswa yang diajar guru laki-laki dan guru perempuan (thitung= 4,610)>ttabel=1,980). Tidak terdapat perbedaan kemampuan mengajar yang signifikan antara guru yang sudah bersertifikasi dengan guru non-sertifikasi, guru laki-laki menghasilkan siswa dengan rata-rata nilai ulangan umum lebih baik dibanding guru perempuan. Disarankan peninjauan ulang sistem sertifikasi guru.